Preliminary Investigation into the Association between Scoliosis and Hypoxia: A Retrospective Cohort Study on the Impact of Eliminating Hypoxic Factors on Scoliosis Outcomes - Ugur, Fatih; Topal, Kubra; Albayrak, Mehmet; Taskin, Recep; Topal, Murat (MDPI AG, 2024)
Objective: This study delves into the implications of adenoidectomy for scoliosis progression, investigating the intricate nexus of hypoxia, spinal curvature, and surgical intervention. With adenoidectomy being a common procedure for addressing pediatric sleep-disordered breathing, this research study explores its potential impact on spinal health. Patients and Methods: Employing a retrospective cohort design, this study gathered data from patients who underwent adenoidectomy, including those with scoliosis, between January 2017 and March 2023. Initial and follow-up evaluations involved clinical and radiological assessments, notably measuring the Cobb angle to quantify spinal curvature. Results: This study enrolled 218 patients under 10 years old. Among them, 18 exhibited Cobb angles of 10° or more, with a mean Cobb angle of 12.8°. In the follow-up evaluation, 83% of patients with initial Cobb angles of 10° or more were reached out to, along with 84.6% of those with Cobb angles below 10°. The postoperative follow-up revealed a notable decrease in Cobb angles for most patients, particularly those with an initial Cobb angle exceeding 10°. Conclusions: This study underscores the potential connection between adenoidectomy, hypoxia, and scoliosis regression, highlighting the importance of early intervention for scoliosis management. Despite certain limitations, this investigation lays the foundation for future research involving larger patient cohorts and multifaceted analyses. The observed interactions between airway function, hypoxia, and spinal health open avenues for refining clinical strategies in scoliosis treatment.
Keywords: adenoidectomy; Cobb angle; scoliotic attitude; Pediatrics; RJ1-570; Article